The foundations of spelling ability: Evidence from a 3-year longitudinal study - Caravolas, M; Hulme, C; Snowling, M (2001)
The development of spelling skills was investigated at four points over the first 3 years of schooling in 153 British children. In order to uncover the developmental relationship between spelling and reading ability and to identify the component skills of spelling, children were assessed with a large battery of tests, including reading, phoneme awareness, letter-sound and letter-name knowledge, memory, and verbal and nonverbal IQ. Spelling productions were assessed both for phonological plausibility and for conventional accuracy. A path analysis revealed that phoneme segmentation and letter-sound knowledge were the precursor skills of early phonological spelling ability; in turn phonological spelling combined with reading to promote conventional spelling skill. Although initial phonological spelling ability predicted later reading, early reading ability did not influence later phonological spelling ability. These results indicate that skilled spelling requires a foundation in phonological transcoding ability which in turn enables the formation of orthographic representations. Our data also suggest that the increasingly complex and specific orthographic patterns demonstrated in children's spelling are learned through experience and instruction in both reading and spelling. © 2001 Academic Press.